Synthesis of b-Amino Cyclone Catalyzed by Alkaline Al2O3 - Xu, W.F.; Chen, Q.; Liu, R.Q.; Ren, F.B.; Zhou, Y.F.; Lu, X.L. (Asian Journal of Chemistry, 2011)
A new method for the synthesis of b-amino cyclone with amines and cyclonene, which was efficiently carried out under solvent free conditions in a short time at room temperature using the catalyst of alkaline Al2O3 with high yield. The reusability of the catalyst has been successfully examined without noticeable loss of its catalytic activity.